A case report of an excellent response to interferon- α in a patient with functional metastasized neuroendocrine tumor refractory to other treatments. Issue 25 (19th June 2020) - Özdirik, Burcin; Tacke, Frank; Benz, Fabian; Amthauer, Holger; Fehrenbach, Uli; Roderburg, Christoph; Jann, Henning
Abstract: Introduction: Interferon alpha (IFNα) has been used for a long time in patients with functionally active neuroendocrine tumors (NET). However, due to the unfavorable toxicity profile of interferon, the perceived limited efficacy as well as the development of novel substances, IFNα is only used sparingly in the treatment of NET to date. Patients concerns and diagnosis: We describe the case of a 63-year-old male patient with highly differentiated, functional NET of the ileum and synchronous liver metastasis. Interventions: After failure of classical therapies including dose-intensified somatostatin analog treatment and palliative primary tumor resection, a therapy with pegylated IFNα2a (135 μg/wk) was initiated. Following this treatment, the patient fully recovered from signs of hypersecretion and demonstrated an impressive tumor response. Outcomes: Thirty months after initiating IFNα, the patient is still free of clinical symptoms and shows a sustained tumor response. Notably, no relevant side effects were observed. Conclusion: Our case report supports the use of IFNα in patients with functional NET refractory to classical treatments.